Maximum principles, Liouville-type theorems and symmetry results for a general class of quasilinear anisotropic equations - Barbu Luminita; Enache Cristian (Advances in Nonlinear Analysis, 2016)
This paper is concerned with a general class of quasilinear anisotropic equations. We first derive some maximum principles for two appropriate P-functions, in the sense of Payne (see the book of Sperb [18]). These maximum principles are then employed to obtain a Liouville-type result and a Serrin–Weinberger-type symmetry result.